Glycerine pitch from glycerine concentration process as alternative fuel for boiler operations - Merapan, Kirubaharan (2015)
The usage of energy in world is increasing rapidly where the industries accounts 50% of world energy uses. Palm based oleo chemical are producing series of products such as fatty acid,methyl esters,fatty alcohols and glycerine which means that oil palm industries generate a number of wastes too and the estimated oil palm waste contribute RM 6379 million of energy annually. Glycerine pitch has a calorific value of about 3300kcal/kg. This research is focused on utilizing energy in glycerine pitch by using it as fuel in boiler for both economical and environmental reason. Glycerine pitch is classified as a waste under Schedule S181 of the Environmental Regulations in Malaysia where the treated glycerine pitch is disposed in landfills. Glycerine pitch will be blend with diesel at the ratio of 20:80, 30:70, 40:60, and the calorific value of each blend of diesel and glycerine pitch will be determined. The mixture of glycerine fuel and diesel is known as blend 20:80, blend 30:70 and blend 40:60.The blend fuels are used as fuel in boiler and after firing, flue gas temperature and emission level is determined using combustion analyzer. Lastly,the limitation and advantages of using glycerine pitch as fuel in boiler is compared with natural gas.